DEVELOPMENT OF A DISCOVERY LEARNING-BASED STUDENT WORKSHEET (LKPD) TO IMPROVE STUDENTS' ANALYTICAL SKILLS IN THE AQIDAH AKHLAK SUBJECT ON THE QADHA AND QADAR MATERIAL FOR NINTH GRADE AT MTS AS-SHOFA - Habsah Febiyanti Saragih; Sayed Akhyar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Learning of Aqidah Akhlak at MTs As-Shofa is still dominated by lectures and conventional worksheets, so students' analytical skills regarding the Qadha and Qadar material have not developed optimally. This study aims to develop Student Worksheets (LKPD) based on Discovery Learning to improve students' analytical skills in the Akidah Akhlak subject, specifically on the Qadha and Qadar material for ninth-grade students at MTs As-Shofa. The method used was Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). The research subjects were all 30 ninth-grade students, selected using total sampling with a one-group pre-test post-test design. The instruments included an expert validation sheet, teacher and student response questionnaires, and Higher-Order Thinking Skills (HOTS)-based essay questions. The results showed an average validity of 98.13% (highly valid), practicality of 96.57% (highly practical), and an N-Gain of 73% (high classification), with the average pretest score of 48.33 increasing to 86.17 on the posttest, and 93.33% of students achieving the high N-Gain classification. Thus, the Discovery Learning-based worksheets developed were proven to be valid, practical, and effective in improving students' analytical skills regarding the subject matter of Qadha and Qadar.